Politeness Strategies Implied in the Online Marketplace Comment Section of the Instagram Account @amazondotin - Bahaiyathul Muslimah; Richie, Novito; Salwa, Siti; Herawati, Silvia Arian; Suhayati, Lisa (EDULIA: English Education, Linguistic and Art Journal, 2026)
This research aims to analyze the politeness strategies used by netizens in the comment section of the Instagram account @amazondotin by applying Brown and Levinson’s Politeness Theory (1987). Using a qualitative descriptive method, the researchers collected comments from 17 Instagram posts and categorized them into four politeness strategies: bald on-record, positive politeness, negative politeness, and off-record. The findings reveal a total of 52 identified strategies, with bald on-record being the most dominant (36.54%), followed by positive politeness (26.92%), negative politeness (25%), and off-record (11.54%). These results indicate that users on e-commerce social media platforms tend to communicate directly, especially when expressing urgency or dissatisfaction, while politeness markers appear depending on contextual and intentional factors. Overall, the study concludes that digital communication in marketplace settings blends directness with socially motivated politeness strategies, reflecting users’ attempts to balance clarity, efficiency, and interpersonal consideration.